2009
DOI: 10.1158/0008-5472.can-09-1404
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Inhibitors Activate the Proto-Oncogene Ras and Promote Protumorigenic Signals in Renal Cancer Cells

Abstract: The development of cancer is a major problem in immunosuppressed patients, particularly after solid organ transplantation. We have recently shown that calcineurin inhibitors (CNI) used to treat transplant patients may play a critical role in the rapid progression of renal cancer. To examine the intracellular signaling events for CNI-mediated direct tumorigenic pathway(s), we studied the effect of CNI on the activation of proto-oncogenic Ras in human normal renal epithelial cells (REC) and renal cancer cells (7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 49 publications
3
57
0
1
Order By: Relevance
“…However, the regulatory mechanism(s) of HO-1 overexpression in cancer cells, including renal cancer, is not well defined. Previously, we have shown that the proto-oncogene H-Ras is activated in human renal cancer cells following immunosuppressive therapy, and the activated H-Ras can mediate proliferation of tumor cells (37). In this study, for the first time, we demonstrate that activated H-Ras can promote HO-1 transcriptional activation and protein overexpression in renal cancer cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, the regulatory mechanism(s) of HO-1 overexpression in cancer cells, including renal cancer, is not well defined. Previously, we have shown that the proto-oncogene H-Ras is activated in human renal cancer cells following immunosuppressive therapy, and the activated H-Ras can mediate proliferation of tumor cells (37). In this study, for the first time, we demonstrate that activated H-Ras can promote HO-1 transcriptional activation and protein overexpression in renal cancer cells.…”
Section: Discussionsupporting
confidence: 55%
“…We have recently demonstrated that H-Ras becomes activated in human renal cancer cells under stress following treatment with immunosuppressive agents, and the activated H-Ras induces tumorigenic pathways (37). We have also observed that the expression of HO-1 is significantly up-regulated in renal cancer tissues, and the overexpressed HO-1 can inhibit tumor cell apoptosis (38).…”
mentioning
confidence: 99%
“…switch on oncogenes to promote cancer cell proliferation, survival and metastasis (41,42). A number of retrospective studies have demonstrated a dose related association between CNI IS and HCC recurrence after liver transplant (16,27,43).…”
Section: Calcineurin Inhibitors (Cnis)mentioning
confidence: 99%
“…EBV-infected lymphocytes) to initiate re-activation of latent infection (Ryffel et al, 1992). Other reports have described the role of calcineurin inhibitors in activation of proto-oncogenic RAS (Datta et al, 2009). Indeed, these compounds may also be useful in the MHV-68 model and have already been tested with cyclosporine A (CsA).…”
Section: Drug-induced Immunosuppressionmentioning
confidence: 99%